PENGARUH PENAMBAHAN SUSU SKIM PADA BERBAGAI LEVEL TERHADAP KUALITAS PRODUK HOMEMADE YOGURT YANG MENGGUNAKAN YOGURT PLAIN SEBAGAI STARTER - Andreas Do Lebha (Jurnal Sains Peternakan, 2013)
The purpose of this study were to know the influence of increased skim milk in various levels to the quality of yogurt homemade product by used yogurt plain as the starter. This research was conducted on 6th December 2013 up to 6th January 2014 in animal husbandry faculty of Kanjuruhan University laboratory. The method of this study was analyzed based on Completely Randomized Design (CRD) which each treatment are redone at eight times. The result of this research show that the increased of skim milk in level 2.5 % were the high rate of protein were 4.40% and the increased skim milk in level 1,5% were the lowest rate of protein were 3.70%. From the result of this research can be conclude that there is any significant influence of the rate of protein in each treatment (p<0.01) while the test of yogurt which were done in organoleptik showed that there are no significant influence of increasing skim milk based on the level of interest, color, and taste. Key words: Starter, skim milk, yogurt plain, milk cow, fermentation.